Use Of Black Solanum (Solanum Nigrum.) In Folk Medicine (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
People have encountered various phenomena in their daily lives, learned whether a plant is sweet or sour, tasteless or delicious, poisonous or non-poisonous. As a result, they began to pay attention to the medicinal properties of plants. Medicinal plants are widely and rationally used in folk and scientific medicine. Medicinal properties are also present in many types of weeds, and these properties have been studied as a result of research conducted by scientists. In this article, we would like to provide information about the medicinal properties of one of such plants, black solanum.